Women’s Roles in Enhancing Food Security Through Postharvest Management Among Tharu Indigenous Communities - Chaudhary, Buddhi Ram; Acciaioli, Greg; Chaudhary, Pashupati; Chaudhary, Sunita; Erskine, William (Dhaulagiri Journal of Sociology and Anthropology, 2025)
Postharvest loss in agriculture is considerably high in developing countries due to the lack of infrastructure and technology. Changes in agricultural practices and climate variability further aggravate the risks of postharvest losses. Postharvest loss can be minimized using technologies, including generationally tested local knowledge of Indigenous Peoples, where women play critical roles. Despite its significance in developing new knowledge and technologies, Indigenous knowledge in postharvest management and its resiliency to climate change, particularly the contribution of women, is poorly documented in Tharu communities in Nepal. This paper thus documents the roles of Tharu women and Tharu Indigenous knowledge to ensure food security and promote resilient agriculture in general and postharvest improvement in particular. The study utilized qualitative research methods to explore and document postharvest management practices and technologies of the Tharu from gendered perspectives, considering cases from the eastern region (Bara), central region (Chitwan), and western region (Bardiya) of Nepal. The research revealed that the Tharu have locally evolved postharvest practices and technologies, such as sun drying after harvest and dehari or kothi grain storage technology, that minimize postharvest losses from insects, fungus, rodents, and climatic stresses. Women are central in postharvest processing, storage, and conserving seed grain. Therefore, development approaches that enhance women’s knowledge, capacity, and efficiency in agricultural postharvest management can contribute to household and community food security and income.